Effects of Therapist Feedback on the Therapeutic Alliance and Alcohol Use Outcomes in the Outpatient Treatment of Alcohol Use Disorder. (1st March 2020) - Maisto, Stephen A.; Schlauch, Robert C.; Connors, Gerard J.; Dearing, Ronda L.; O'Hern, Kelly A.
Abstract : Background: It is widely accepted that the therapeutic alliance (TA) is a mediator of psychotherapy effects, but evidence is sparse that the TA is an actual mechanism of behavior change. The purpose of this study was to provide the first systematic evidence regarding the TA as a mechanism of change in the treatment of alcohol use disorder (AUD). Methods: Participants were 155 adult men and women presenting for individual outpatient treatment of AUD. Each was randomly assigned to 1 of 6 experienced therapists, who did or did not receive over 3 study phases postsession participant feedback on his/her ratings of the TA. All participants received a 12‐session version of cognitive behavioral therapy for AUD. Participants rated the TA by use of the California Psychotherapy Alliance Scale (CALPAS) and reported their daily alcohol consumption between sessions and for 1 year posttreatment by use of the timeline followback interview. Multilevel statistical models that partitioned within‐ and between‐participant effects and between‐therapist effects were run to test the effects of feedback condition on the alliance and alcohol use, and the effects of the alliance on alcohol use. Results: The study's main hypotheses that feedback causes an enhanced therapeutic alliance and that the alliance is associated with better alcohol use outcomes were not supported. Conclusions: Several methodological and substantive reasons for the pattern of findings are suggested, as well as directions for future research that would advance study of the TA as a mechanism of change in psychotherapy and in studying therapist effects on outcomes in general. Abstract : This study highlights the importance of several factors that might be incorporated in research designs to study the therapeutic alliance as a mechanism of alcohol use disorder treatment‐related changes in alcohol use and related outcomes.